Small scale habitat effects on anthropogenic litter material and sources in a coastal lagoon system - Velez, Nadja (2021)
Anthropogenic litter is ubiquitous throughout marine ecosystems, but its abundance and distribution are driven by complex interactions of distinct environmental factors and thus can be extremely heterogeneous. Here we compare the extent of anthropogenic litter pollution at a sheltered lagoon habitat and nearby open coast sites. Monthly surveys over a period of five months showed that both the types and sources of litter always differed significantly between lagoon and open coast sites. Pollution within the lagoon was mainly land-derived and was largely made up of construction materials (70% to 95%). At open coast sites, construction materials represented a minor portion of pollution (4% to 12%) while plastics were the most abundant (82% to 95%). We show that stranded anthropogenic litter in adjacent marine habitats can differ significantly and stress the importance of sampling at appropriate spatial scales to gain realistic insights into the sources of pollution.